2016
DOI: 10.1186/s11671-016-1466-x
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis of the Optical and Charge Transport Properties of Ultrasonic Spray Pyrolysis-Grown Zinc Oxide/Graphene Hybrid Structures

Abstract: We demonstrate a systematic computational analysis of the measured optical and charge transport properties of the spray pyrolysis-grown ZnO nanostructures, i.e. nanosphere clusters (NSCs), nanorods (NRs) and nanowires (NWs) for the first time. The calculated absorbance spectra based on the time-dependent density functional theory (TD-DFT) shows very close similarity with the measured behaviours under UV light. The atomic models and energy level diagrams for the grown nanostructures were developed and discussed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…The measured sensing characteristics suggest that the synthesized Pt NPs are able to act as the effective cracking catalyst to allow the absorption of H 2 even though the deposited thickness of 16 nm is relatively thick and the H 2 concentration of 0.5% is low. The obtained results are comparable with the other reported works (Ali & Hashim 2016;Phan & Chung 2014).…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…The measured sensing characteristics suggest that the synthesized Pt NPs are able to act as the effective cracking catalyst to allow the absorption of H 2 even though the deposited thickness of 16 nm is relatively thick and the H 2 concentration of 0.5% is low. The obtained results are comparable with the other reported works (Ali & Hashim 2016;Phan & Chung 2014).…”
Section: Introductionsupporting
confidence: 83%
“…In this work, the annealing is performed under N 2 at annealing temperature beyond 500°C which tends to decompose the graphene matrix, where certain part of sp 2 bonds in graphene start to break resulting to the graphitic formation (Phan & Chung 2014). Such decomposition of graphene matrix will deteriorate the charge transport property to certain extent and hence the conductivity of the entire structure will be reduced (Ali & Hashim 2016;Phan & Chung 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen in the figure, the electrostatic potential depends strongly on structure, as has been mentioned in our work. (75)(76)(77) We found that the transport time for electrons differs by about 10 orders of magnitude between nanorods and nanosphere clusters. (75) The use of graphene as an interface layer in the ZnO-decorated sensor is the main reason behind the sensitivity of the transport properties to the volumetric changes in the structures.…”
Section: Transport In Nanoporous Membranes Composite Electrodes Andmentioning
confidence: 92%
“…(75)(76)(77) We found that the transport time for electrons differs by about 10 orders of magnitude between nanorods and nanosphere clusters. (75) The use of graphene as an interface layer in the ZnO-decorated sensor is the main reason behind the sensitivity of the transport properties to the volumetric changes in the structures. Detailed information based on X-ray absorption measurements (XAS), from the bulk and the surface on the degree of carbon sp 3 /sp 2 hybridization and oxygen functional groups in two different C thin films is presented in the following.…”
Section: Transport In Nanoporous Membranes Composite Electrodes Andmentioning
confidence: 92%
See 1 more Smart Citation